National patterns of paroxetine use among US Medicare patients from 2015–2020 - Cavanah, Luke R.; Goldhirsh, Jessica L.; Huey, Leighton Y.; Piper, Brian J. (Frontiers in Psychiatry, 2024)
Introduction: Paroxetine is an older “selective” serotonin reuptake inhibitor (SSRI) that is notable for its lack of selectivity, resulting in an anticholinergic adverse-effect profile, especially among older adults (65+). Methods: Paroxetine prescription rates and costs per state were ascertained from the Medicare Specialty Utilization and Payment Data. States’ annual prescription rate, corrected per thousand Part D enrollees, outside a 95% confidence interval were considered significantly different from the average. Results: Nationally, there was a steady decrease in population-corrected paroxetine prescriptions (-34.52%) and spending (-29.55%) from 2015-2020 but a consistent, five-fold state-level difference. From 2015-2020, Kentucky (194.9, 195.3, 182.7, 165.1, 143.3, 132.5) showed significantly higher prescriptions rates relative to the national average, and Hawaii (42.1, 37.9, 34.3, 31.7, 27.7, 26.6) showed significantly lower prescription rates. North Dakota was often a frequently elevated prescriber of paroxetine (2016: 170.7, 2018: 143.3), relative to the average. Neuropsychiatry and geriatric medicine frequently prescribed the most paroxetine, relative to the number of providers in that specialty, from 2015-2020. Discussion: Despite the American Geriatrics Society’s prohibition against paroxetine use in older adults and many effective treatment alternatives, paroxetine was still commonly used in the US in this population, especially in Kentucky and North Dakota and by neuropsychiatry and geriatric medicine. These findings provide information on the specialty types and states where education and policy reform would likely have the greatest impact on improving adherence to the paroxetine prescription recommendations.